Production and turnover of microbial organic matter in surface intertidal sediments. (July 2018) - Wu, Weichao; Meador, Travis; Hinrichs, Kai-Uwe
Highlights: Microbial growth in surface sandy sediments ranged from 17 to 64 µg C/gdw /yr. Microbial heterotrophic activity could explain dark inorganic carbon fixation in sandy sediments. High microbial growth rate invoked high turnover of TOC and/or DOC in the sandy sediment. Abstract: Benthic microorganisms play a significant role in the remineralization of sedimentary organic matter (OM). In order to constrain the growth rate, turnover and carbon metabolism of microbial communities in anoxic sandy sediments, we quantified the rate of inorganic carbon (IC) assimilation and of lipid production via a recently developed dual isotope-labelling assay that can differentiate autotrophic vs. heterotrophic production in a 22 cm sediment core from the Janssand tidal flat (Wadden Sea, Germany). Despite an extremely low concentration of total organic carbon (TOC) in the majority of samples (<0.3%), the concentration of total fatty acids (TFAs) was in the range 4.5 to 28.4 μg/mg TOC, suggestive of a high contribution of fresh microbial and algal biomass to the TOC pool. This was corroborated by a production rate of microbial FAs, which ranged from 0.3 to 4.7 μg TFAs/gdw /yr (where dw = dry wt) and the mean turnover time of microbial FAs was 6 ± 5 yr. The enhanced production rate of iso- and anteiso- branched FAs was consistent with the presence of an active population of sulfate reducing Deltaproteobacteria . The assimilation rate of IC into bacterial lipids was relatively low (0.16 ± 0.07 μg C/gdw /yr) in OM-lean sandy sediments (i.e. upper 17 cm), such that the IC assimilation to lipid production ratio values was typically <0.3, indicating that heterotrophic bacteria were dominant and dark IC fixation played a minor role at the study site. The measured rates of FA production converted to an anaerobic heterotrophic C demand of 0.4–1.8 µg C/gdw /d, assuming a bacterial growth efficiency of 10%. Such high biomass proportion, production rate and C demand suggested that dissolved OM must play a vital role in sustaining the active heterotrophic microbial populations in these sandy sediments.